2018
DOI: 10.1002/jcb.26902
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA LOC554202 promotes laryngeal squamous cell carcinoma progression through regulating miR‐31

Abstract: Laryngeal squamous cell carcinoma (LSCC) is one aggressive malignancy and accounts for 20% of all head and neck cancer. However, the role of LOC554202 in human LSCC remains unknown. The expression level of LOC554202 and miR-31 was detected in the LSCC tiussues by using qRT-PCR. Cell growth was measured by CCK-8 assay. Flow cytometry and matrigel-coated membrane was used to detect for cell cycle and invasion respectively. We indicated that lncRNA LOC554202 expression was overexpressed in LSCC tissues compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 35 publications
3
53
0
Order By: Relevance
“…TUG1-knockdown has been associated with cell cycle arrest in G 0 /G 1 phase (14). Glioma has been reported to be the most common type of primary cerebral tumor (1).…”
Section: Discussionmentioning
confidence: 99%
“…TUG1-knockdown has been associated with cell cycle arrest in G 0 /G 1 phase (14). Glioma has been reported to be the most common type of primary cerebral tumor (1).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA MIR31HG, locating at human chromosome 9p21.3 [40] with transcription regulated by methylation of the promoter region [27], was found aberrantly expressed in several types of cancers. Specifically, MIR31HG was found elevated expressed in breast cancer [13], cervical cancer [28], chordoma [16], osteosarcoma [15], lung cancer [2,23,41], OSCC [4], PDAC [7], VSCC [29] and LSCC [36,42,43]. Nevertheless, the expression levels of MIR31HG was reported down-regulated in triple-negative breast cancer (TNBC) cell lines of basal subtype [27], bladder cancer [26], gastric cancer [25], CRC [32,33], and HCC [6].…”
Section: Discussionmentioning
confidence: 99%
“…For example, MIR31HG could enhance proliferation, migration and invasion by up-regulating EZH2/miR-31 and then indirectly activating the oncogene RNF144B in chordoma [16]. Yang et al demonstrated that elevated MIR31HG could inhibit miR-31 expression, and increase RhoA in LSCC, and via which promote cell growth, cell cycle and invasion [43]. In addition to miR-31, other miRNAs were also identified to interact with MIR31HG in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence have verified that the abnormal expression of lncRNAs is associated with tumor initiation. For example, TUG1, overexpressed in oral squamous cell carcinoma cells (Yan, Wang, Yang, Lu, & Zhou, 2017) and BANCR, upregulated in colorectal cancer cells, were associated with poor prognosis (Shen, Bai, Luo, & Zhou, 2017). Similarly, numerous studies reported that lncRNAs, as ceRNAs for miRNA, played a significant role in modulating HCC cell tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%